Liver diseases (Review of the Seventeenth Russian Gastroenterological Week proceedings, October, 10–12, 2011, Moscow) - I. V. Mayev; A. N. Kazyulin; Yu. A. Kucheryavy; Ye. A. Mayevskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2012)
The aim of review. To analyze proceedings of the Seventeenth Russian Gastroenterological Week (October, 10–12, 2011, Moscow), published in the «Liver» partition (Ros. zhurn. gastroenterol. gepatol. koloproktol. – 2011. – Vol. 21, N 5. – Suppl. 38).Original positions. Analysis of 149 abstracts accepted for publication as proceedings of the Seventeenth Russian Gastroenterological Week was carried out. The most of publications (70,5%) has been devoted to etiopathogenesis, features of clinical pattern, diagnostics and treatment of acute and chronic viral hepatitis (2542 patients), liver cirrhoses (1338 patients), non-alcoholic fatty liver disease (1145 patients), toxic liver diseases (834 patients) that indicates medical and social impact of these diseases. Statistical analysis, allowing to make any conclusions on studies represented by the abstract, was contained in 44 abstracts of 149, submitted in the «Liver» section (29,5%). Other publications, some from which are invoked major interest, unfortunately, still remain to be only descriptive researches and experts opinions, that requires improvement quality of the theses presented by authors, first of all by compliance with requirements for publication and presentation of statistical analysis results.